Profit Maximization and the Extinction of Animal Species - Clark, Colin W. (Journal of Political Economy, 1973)
In this paper I construct and analyze a simple mathematical model for the commercial exploitation of a natural animal population. The model takes into account the response of the population to harvesting pressure, the increasing harvesting costs associated with decreasing population levels, and the preference of the harvesters for present over future revenues. The principal conclusion of the analysis is that, depending on certain easily stated biological and economic conditions, extermination of the entire population may appear as the most attractive policy, even to an individual resource owner.